Pattern discovery in annotated dialogues using dynamic programming. (1st January 2012) - Lecroq, Thierry; Pauchet, Alexandre; Chanoni, Émilie; Solano, Gerardo Ayala
This study describes a new heuristic to discover behavioural patterns in annotated dialogues: firstly, dialogues are transcribed and annotated; then, two-dimensional patterns are extracted; finally, the semantic pertinence of the extracted patterns can be evaluated by an expert. The dialogues are annotated by using a grid designed by the expert. Recurrent patterns are extracted in the annotated dialogues using dynamic programming with the help of a substitution matrix specifically designed for the task. This article focuses on the method developed for extracting the patterns and presents as application some extracted patterns on annotations of dialogues between parents and children during the narration of child stories.